(untitled) (Perner’s Contacts, 2007)
Customer with his requirements is coming on the central demand in the field passenger transportation too. Customer evaluates the needs of transporting only as a part of the transfer process and his interest is to make this process effectively, quality, and cost effective. Process portal supported by the CRM software solution make possible for the railway operator the supporting of the whole transportation process and orientation to the individual customers requests by the using of the modern information technologies with a view to obtain the loyal customers in a long term. The paper deals with the propose of the process portal operation by the railway transport operator.